Unnatural ability : the history of performance-enhancing drugs in thoroughbred racing - Toby, Milton C. (Horses in history (University Press of Kentucky), 2023)
"In 2021, horse racing's most recognizable face-Hall of Fame trainer Bob Baffert-had five horses that failed postrace drug tests, including that year's Kentucky Derby winner, Medina Spirit. While the incident was a major scandal in the Thoroughbred racing world, it was only the latest in a long string of drug-related infractions among high-caliber athletes. Stories about systemic rule-breaking and "doping culture"-both human and equine-have put world-class athletes and their trainers under intense scrutiny. Each newly discovered instance of abuse forces fans to question the participants' integrity, and in the case of horse racing, their humanity. In Unnatural Ability: The History of Performance-Enhancing Drugs in Thoroughbred Racing, Milton C. Toby addresses the historical and contemporary context of the Thoroughbred industry's most pressing issue. While early attempts at boosting racehorses' performance were admittedly crude, widespread legal access to narcotics and stimulants has changed the landscape of horse racing, along with athletic governing bodies' ability to regulate it. With the sport at a critical turning point in terms of doping restrictions and sports betting, Toby delivers a comprehensive account of the practice of using performance-enhancing drugs to influence the outcome of Thoroughbred races since the late nineteenth century. Paying special attention to Thoroughbred racing's purse structure and its reliance on wagering to supplement a horse's winnings, Toby discusses how horse doping poses a unique challenge for gambling sports and what the industry and its players must do to survive the pressure to get ahead"--